Bahasa Inggris - Ria Septiana; Agung Priyo Utomo (Jurnal Ketenagakerjaan, 2025)
Unemployment is an economic problem that triggers social impacts such as crime and poverty. In 2024, Java Island recorded the highest rate of educated youth unemployment compared to other islands, particularly in urban areas. This is a critical issue, as educated young people are a vital asset in a nation’s economic development, whose potential can be harnessed to achieve Indonesia’s vision for 2045. Therefore, the objective of this study is to examine the general status of unemployment among educated youth, as well as the influence of individual and regional factors on unemployment among educated young people in urban areas of Java Island in 2024. This study utilizes data from the National Labor Force Survey (Sakernas), August 2024 Labor Force Conditions Publication, and the 2025 District/City in Figures Publication. A two-level binary logistic regression analysis was employed to examine the individual and contextual factors influencing the unemployment status of educated youth in urban areas. The findings indicate that the labor force that has never participated in certified training and resides in areas with a large labor force has a greater risk of being unemployed. Therefore, this study is expected to assist the government in formulating policies to minimize youth unemployment, particularly among those with at least a high school education or its equivalent in urban areas of Java Island.